CommunityBased Politics: Empowering Women’s Leaders in Yogyakarta - Any Sundari (Yayasan Jurnal Perempuan, 2014)
Women’s participation in politics is a crucial discourse in Indonesia. Affirmative action policy by providing 30% quota for women in parliament is a positive thing enforcing women to enter into political contestation. However, encouraging women to engage in politics is not easy task. Politics from the outset has been identified as a distinctive world of men and women experienced constant domestication systematically orchestrated by the state. Ibuism ideology caused women to experience a variety of vulnerabilities and bundle of violences in formal politics. To revive women politically especially at the community level, women can learn to negotiate outside of formal politics to voice their representation.